Knockdown of SLCO4C1 inhibits cell proliferation and metastasis in endometrial cancer through inactivating the PI3K/Akt signaling pathway - Hu, Xiang (Oncol Rep, 2020)
Endometrial cancer (EC) is the second leading type of cancer among women, and its progression is dependent on several factors. The aim of the present study was to examine the effect of solute carrier organic anion transporter family member 4C1 (SLCO4C1) on human EC and determine the underlying molecular mechanism. A total of 57 differentially expressed genes associated with advanced stage and survival were identified in The Cancer Genome Atlas database. In addition, gene ontology analysis indicated that SLCO4C1 was highly expressed in cell differentiation and integral component of plasma membrane. High SLCO4C1 expression in EC tissues was verified by immunohistochemistry. The results demonstrated that the downregulation of SLCO4C1 could significantly suppress the viability, sphere formation, migration and invasion abilities of cells, but enhance apoptosis in EC cell lines. Furthermore, the present results demonstrated that SLCO4C1 had effects on the epithelial-mesenchymal transition (EMT) phenotype in EC cells and regulated the expression of EMT-related proteins. Mechanistically, the present study revealed that SLCO4C1 regulated the biological functions of EC cells by inactivating the PI3K/Akt signaling pathway. Collectively, it was demonstrated that the SLCO4C1/PI3K/Akt pathway may play an important role in EC progression and metastasis and serve as a potential biomarker and target for EC diagnosis and treatment.